Preferensi Pengguna terhadap Layanan Bus Rapid Transit (BRT) Purwokerto-Purbalingga - Fauzan Romadlon; Yudha Saintika (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2020)
The objectives of BRT are divided into three aspects; environment, social, and economics  Bus Rapid Transit (BRT) in Purwokerto and Purbalingga is new mass transportation. The route of BRT is from Bulupitu Bus Station to Bukateja Bus Station round trip. Unfortunately, the operation of the BRT is not fully supported by the community, especially ridership. Ridership involvement is very important to support sustainability transportation service. Data collection was carried out from 163 BRT ridership. The method used is descriptive statistics, including ridership demographics and experience. Moreover, parametric statistics are used to determine the level of significance of the relationship between demographic aspects and experience with ridership preferences. The results are in economics preferences, age range and travel time of ridership to the BRT stop are significant. Social preferences are influenced by routine of using BRT, ridership residential, travel time, and ridership waiting time at BRT stops. As environmental preferences criteria are influenced by work and the ridership age range. As a recommendation, BRT operators should improve the quality and quantity of services so that BRT becomes mass transportation that is environmentally friendly and able to meet the needs of the people in these two regions